EFFECTIVENESS OF USING MIXED-LIGAND COMPLEXES OF ZINC, MANGANESE AND COBALT IN FEEDING HIGHLY PRODUCTIVE COWS IN THE EARLY DRY PERIOD - Kropyvka, Yu. G.; Bomko, V. S. (Scientific Progress & Innovations, 2021)
The article presents the results of studying the effectiveness of feeding different levels of mixed-ligand complexes of zinc, manganese and cobalt to high-yielding cows of Holstein, Ukrainian black-spotted dairy and Ukrainian red-spotted dairy breeds in the early dry period and the complex-es’ impact on feed consumption, live weight indicators, postpartum condition, and hematological blood parameters. The research results showed that the best consumption of dry matter (DM) in the diets of cows of the 5th experimental group was due to better eating of hay, silage and haylage – by 3.92 % as compared to the control group. Good consumption of feed by animals ensured the increase in their live weight. Cows of the 1st (control) group increased live weight by 25.1 kg, while the in-crease in cows’ live weight of the experimental groups was higher in comparison with the control by 1.2-9.6 % or 0.3-2.4 kg. The difference was significant for cows of the 4th and 5th experimental groups (P<0.01 – P < 0.001). At lower levels of mixed-ligand complexes of zinc, manganese and cobalt, the concentration of which in 1 kg of DM feed mixture was, in mg: zinc – 27.0; manganese – 27.0; cobalt – 0.34, the live weight of calves in the experimental groups at birth increased by 2.6- 6.6 % in comparison with the control. Also, lower doses of these microelements in the form of mixed-ligand complexes in the diet of pregnant dry cows had a positive effect on their birth rates. In partic u-lar, cows of the experimental groups had a better labor process and no cases of placental retention were detected. Of 10 cows in the control group, 7 heads, or 70 % calved down without outside assis-tance, in the 2nd experimental group – 9 heads, and in the 3rd, 4th and 5th groups – 10 heads from each, or 100 %. Placental separation in all cows of the 3rd, 4th and 5th experimental groups took place in time, in the 2nd experimental group, one cow had placental retention, and in the control group – two. The analysis of hematological parameters of experimental cows has shown that mixed-ligand complexes of zinc, manganese and cobalt in concentrated feeds have a positive effect on the body and health of cows. The most effective was the dose of mixed-ligand complexes of zinc, manga-nese and cobalt with the concentration in 1 kg of DM feed mixture: of zinc – 31.5 mg, manganese – 31.5 mg and cobalt – 0.41 mg.